Some Arabic Inscriptions From Medieval Castles of Jordan: Content and Context Analysis - عموش، معن محمد; الجبور، خالد سليمان (جامعة الشارقة, 2015)
The Ayyubid- Mamluk Muslim rulers built or rebuilt castles in order to defend their borders against the crusaders. During the 12th-13th centuries, they changed hands several times, but were maintained and strengthened mainly by the Muslims, as attested by numerous Arabic inscriptions found incorporated into the buildings. It is important to mention here that Irene A. Bierman’s book entitled Writing Signs: The Fatimid Public Text (1998) has been used as a model to carry out the following discussion, in addition to further studies about medieval castles of Jordan which have been used in the catalogue. The researcher intends to discuss aspects of the languages and context of the inscriptions listed in the catalogue. By far the largest type is the group of foundation and restoration texts, put up to show who had ordered the construction and to stake out territory.
قام الحكام الأيوبيون والمماليك ببناء أو إعادة بناء القلاع من أجل الدفاع عن حدودهم ضد الصليبيين خلال القرنين الثاني والثالث عشر الميلاديين، وعلى الرغم من تغير إدارات القلاع في هذه الفترة عدة مرات، إلا أنه تم الحفاظ على مبانيها وتعزيزها بشكل رئيس من لدن المسلمين، كما تشهد العديد من الكتابات العربية التي حملتها القلاع على جدرانها ومبانيها. ومن المهم أن نذكر هنا أن كتاب "كتابة اللافتات: النص الفاطمي العام 1998" لمؤلفه: إيرين أ. بيرمان قد استخدم نموذجا لتنفيذ المناقشة التالية بالإضافة إلى العديد من الدراسات التي تناولت قلاع القرون الوسطى في الأردن. ويعتزم الباحث مناقشة جوانب اللغة وسياق النقوش المذكورة في النشرة المصورة وهي عبارة عن نقوش تأسيسية وترميمية الهدف منها إظهار أسماء من أمر بالبناء أو الترميم وتبيان المواقع التي خضعت لسلطتهم.
Keywords: الكتابات العربية -- القرون الوسطى -- الكتابات التاريخية -- الأردن